2012
DOI: 10.1016/s1995-7645(12)60148-5
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of toxoplasmosis and rubella in pregnant women attending antenatal private clinic at Ouagadougou, Burkina Faso

Abstract: The diagnosis of toxoplasmosis and rubella is necessary in pregnant women in Burkina Faso because of the low immunization coverage rate of rubella and the high level of exposure to these two infections which can be harmful to the newborn if contracted by women before the third trimester of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
3
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 14 publications
4
37
3
1
Order By: Relevance
“…Our data on seroprevalence of Toxoplasma IgG are in line with another recent study that showed a prevalence rate of 88.7% in pregnant women in Accra [23]. In contrast, a significantly lower rate of 20.3% was determined in Burkina Faso [24]. Whether this discrepancy is based on different test systems applied or different environmental burden with parasites remains to be clarified.…”
Section: Discussionsupporting
confidence: 88%
“…Our data on seroprevalence of Toxoplasma IgG are in line with another recent study that showed a prevalence rate of 88.7% in pregnant women in Accra [23]. In contrast, a significantly lower rate of 20.3% was determined in Burkina Faso [24]. Whether this discrepancy is based on different test systems applied or different environmental burden with parasites remains to be clarified.…”
Section: Discussionsupporting
confidence: 88%
“…A lower prevalence rate was reported from Benin (30.0 %) (De Paschale et al 2014) and Burkina Faso (20.3 %) (Linguissi et al 2012). …”
Section: Western Africamentioning
confidence: 69%
“…Hamilelikte primer toxoplasmosis geliştiğinde şiddetli patolojik defektlere (düşük, ölü doğum, fetal anomali; hidrosefali, koryoretinit vb) yol açabilen konjenital toksoplazmoz gelişebilmektedir (2,(5)(6)(7)(8). Dünyada gebelerde yapılan çalışmalarda T.gondii IgG antikor seroprevalansının %20,3 ile %79,8 arasında değiştiği görülmektedir (6,7,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Bu farklılık, bölgesel risk faktörlerinin çeşitlilik göstermesinden kaynaklanmaktadır.…”
Section: Introductionunclassified